Primary cardiac angiosarcoma in a 25-year-old man: excision, adjuvant chemotherapy, and multikinase inhibitor therapy - Bellitti, Renato; Buonocore, Marianna; De Rosa, Nicolina; Covino, Franco Enrico; Casale, Beniamino; Santè, Pasquale (Texas Heart Institute journal, 2013)
Primary cardiac tumors do not occur frequently, and only one quarter of them, chiefly sarcomas, are malignant. Patients with angiosarcoma typically have a shorter survival time than do patients with other sarcomas, and the prognosis for survival depends strictly on the stage of the disease at the time of diagnosis and the possibility of complete surgical excision. Chemotherapy and radiotherapy have well-established postoperative roles because of the high probability of metastasis. We report the case of a 25-year-old man who presented with pericardial effusion and echocardiographic evidence of an intracavitary right atrial mass but without the bulky, infiltrative growth typical of this location of the disease. Malignancy was suggested by the clinical presentation, the location of the mass in the right side of the heart, and the absence of conditions favoring thrombus formation. After complete surgical excision, the mass was confirmed to be an angiosarcoma. Conventional adjuvant chemotherapy and maintenance therapy with inhibitors of CD117 (c-kit) and vascular endothelial growth factor relieved the patient's clinical symptoms and enabled his long-term, disease-free survival. In addition to reporting this case, we discuss aspects of the diagnosis and treatment of angiosarcoma.